Shaping the Future of Behçet’s Uveitis Management: A Comprehensive Review of Efficacy, Challenges, and Prospects of Biologic Therapies - Biao Li; Haoran Li; Qun Huang; Yanlin Zheng (Ophthalmology and Therapy, 2023)
Abstract Behçet’s uveitis (BU), a vision-threatening manifestation of Behçet’s disease, poses substantial management challenges due to its chronic, relapsing nature and potential for vision loss. This review explores the role of biologic therapies in the treatment of BU, providing a comprehensive overview of their effectiveness, drawbacks, and future possibilities. Traditionally, management has relied heavily on corticosteroids and conventional immunosuppressants. However, their long-term use is frequently associated with systemic side effects and insufficient control of ocular inflammation. Biologic therapies, particularly TNF-alpha inhibitors like infliximab and adalimumab, have emerged as effective alternatives, offering better disease control and a more favorable safety profile. We critically evaluated these agents, noting their clinical efficacy in reducing inflammatory flares and preserving visual acuity. Despite their benefits, several issues remain. Accessibility, cost, and lack of long-term safety data limit their widespread use. Additionally, individual variability in treatment response necessitates personalized therapeutic strategies. Recent research has shown promise in addressing these challenges, with the emergence of novel biologic agents and personalized medicine approaches. In summary, biologic therapies represent a paradigm shift in BU management, contributing to better patient outcomes. Yet, there are significant challenges to be overcome. As we move forward, continued research, development of novel biologic agents, and a precision medicine approach will shape the future landscape of BU treatment.